Inequality of opportunity in child nutrition in Pakistan - Shyamkumar Sriram; Lubna Naz (PLoS ONE, 2025)
Introduction Malnutrition among children is one of the major health challenges in Pakistan. The National Nutritional Survey 2018 revealed that 44% of children are stunted. Different circumstances surrounding a child’s birth can lead to inequality of opportunity in early childhood, with significant nutritional inequalities between rural and urban areas. This study aims to identify the drivers of inequality of opportunity in stunting among children under-five years of age in Pakistan. Methods This study used Pakistan Demographic and Health Survey, 2017–18 to identify the factors contributing to inequality of opportunity in child’s stunting. The Dissimilarity index (D-index), along with Oaxaca decomposition, and Shapely decomposition were employed to measure and decompose inequality in opportunity in stunting. Regional variations in stunting among children under various circumstances were analyzed using Geographic Information System or GIS. Results The burden of stunting is exceptionally high in Pakistan, with the prevalence in rural areas significantly exceeding that in urban areas from 1990 to 2018. Shapley decomposition of the contributors to inequality in opportunity indicates that maternal education accounted for 24% of total inequality among rural children and 44% among urban children. Water and sanitation contributed 22% to overall inequality in rural areas but only 2% in urban areas, highlighting the critical role of inadequate water and sanitation in rural settings. The wealth index was a predominant contributor to inequality both nationally and in urban areas. Southern regions exhibit a higher prevalence of stunting and a greater proportion of households lacking adequate water and sanitation. Additionally, the concentration of uneducated mothers and stunted children is notably high in Balochistan and Sindh. Conclusions The lack of maternal education, inadequate access to water and sanitation services, and lower socio-economic status are key factors contributing to inequality of opportunity in stunting among children under five in Pakistan. Understanding the critical role of these circumstances can help policymakers address the situation and implement concrete steps to enhance equal opportunities for child health.